Anthropogenic activity effect on water quality of epikarst spring in the western part of Gunungsewu Karst Area, Java Island, Indonesia - Riyanto, Indra Agus; Cahyadi, Ahmad (Brawijaya University, 2023)
Epikarst springs are the main source of water used by the community in the western part of Gunungsewu Karst Area. One of the springs found in Gunungsewu karst area is Guntur Spring, with a catchment area that functions as agricultural land and settlements. Guntur Spring has connectivity between swallow holes and karst windows, so the spring can easily be polluted; therefore, a temporal study is needed regarding the water quality. The methods used were analysis of water quality standards, Schoeller diagrams, triangular Piper diagrams, and scatter plots. The results of the analysis of water quality standards showed that only Ca2+ and HCO3- ions and a small portion of Na+ exceeded WHO standards. The results of the Schoeller diagram analysis showed that the dominant ions were Ca2+ and HCO3-. The results of the Piper diagram analysis showed that the Guntur Spring is included in the classification of types I, J, and M, indicating the spring is not polluted. The results of the Piper diagrams showed that Guntur Spring is included in the dominant types of types C, A, G, D, and F, indicating the springs are not included in the polluted category. The scatter plot analysis of the Ca2+ + Mg2+ versus HCO3- + SO42- showed that the dominant ion in the Guntur Spring came from the dissolving of limestone. The scatter plot analysis of HCO3- versus Na+ indicated that the main process that forms Guntur Spring ions is not the dissolving process of silicates. The scatter plot analysis of Cl- - SO42- versus Na+ indicated that the main process that forms Guntur Spring ions is not the dissolving process of sodium/sodium sulfate and halite. There was one sample in the Cl- versus Na+ scatter plot analysis that showed an indication of an anthropogenic pollution. However, the overall analysis showed that anthropogenic activities in the study area do have a major impact on the water quality of the epikarst springs at the study site.